YOLK SAC DIAMETER AND EMBRYONIC HEART RATE AS PROGNOSTIC FACTORS OF FIRST TRIMESTER PREGNANCY OUTCOME - H. R., NAMRATHA; K., SOWMYA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Yolk sac is the primary source of exchange between the embryo and the mother before placental circulation and during organogenesis. Yolk sac has immunologic, metabolic, nutritive, endocrine, secretory, excretory and hematopoietic functions. Embryonic heart rate is seen after the appearance of foetal node at 7 w by TAS and 6 w by TVS. Studies have been conducted to establish the importance of yolk sac and EHR in pregnancy outcome. The prognostic significance of the yolk sac for the pregnancy outcome has been assessed with TVS. To measure yolk sac diameter and embryonic heart rate in early pregnancy (less than 10 weeks), to correlate yolk sac measurement and embryonic heart rate individually as prognostic factors for first trimester outcome and to evaluate the measurements in combination as a prognostic marker of first trimester pregnancy outcome. In view of this, the present study was undertaken. Methods: 108 patients attending OPD of Kempe Gowda institute of Medical Sciences Hospital, between 6 to 9 w of gestation, were evaluated with transvaginal sonography and measurements such as CRL, MSD and YSD were taken. Results: The mean age of the study population was 25 y and 88 % of the study population belonged to 20-30 y. 55.6 % of the study population were primigravida. Incidence of abnormal pregnancy outcome was 18.5%. The probability of abnormal outcome increased with the increase in gravidity of the patient (P= 0.890). There was a significant positive comparison of CRL (P= 0.223), GS (P= 0.251) and YSD (P= 0.016). Yolk sac diameter in the first trimester significantly correlates with the pregnancy outcome. An enlarged yolk sac is associated with an increased risk of preterm delivery. Our study influences the pregnancy outcome by the Embryonic heart rate. Foetal bradycardia is an impending sign of foetal death due to chromosomal abnormalities (Trisomy 18), foetal tachycardia featuring Trisomy 21. Conclusion: Yolk sac diameter and embryonic heart rate in the first trimester significantly correlates with the first trimester pregnancy outcome. Thus, the present study indicates that the yolk sac size and the embryonic heart rate is a reliable, beneficial and cost-effective in predicting first-trimester pregnancy outcome. The measurement of the secondary yolk sac diameter between 5th to 9th week of gestation can be used as a valuable tool to predict early pregnancy outcome.